293. Exploring the biomechanical constraints in different pathologies with gait analysis. (December 2018) - Minosse, S.; Pisano, A.; Petrarca, M.; Favetta, M.; Romano, A.; Summa, S.; Castelli, E.
Abstract : Purpose: Aim of this work was to understand the relationship between biomechanical constraints and the development of the gait dynamic functions. Three different pathologies were selected, for analyzing the walking patterns corresponding to a damage of: the first moto-neuron (CP, Cerebral Palsy); the second moto-neuron (CMT, Charcot Marie Tooth); and the muscles (DMD, Duchenne Muscular Dystrophy). Methods: Thirty children affected by CP (10 pts), CMT (10 pts) and DMD (10 pts) underwent a gait analysis with eight-cameras motion capture system (Vicon MX, UK) and two force plates (AMTI, Or6-6, US). Markers were located on anatomical landmarks of the subjects as indicated by Plug-in-Gait protocol to reconstruct a full body model. Three gait cycles were acquired for each patient, the kinematic and kinetic parameters were collected for the lower limb (pelvis, hip, knee and ankle), to describe the biomechanical pattern. Then we looked at the differences between the three pathologies for the spatio-temporal parameters, joints angles, moments and powers that were studied using the Wilcoxon rank sum test. Results: Kinematic and kinetic parameters demonstrated statistically significant differences between these groups. Spatio-temporal parameters were similar between CMT and CP but differed from DMD. The correlation between angle joints in the sagittal plane showed different distributions between pelvis and hip/knee/ankle, while the other joints showed more similar distributions (Fig.). Conclusions: Interestingly CP and DMD walk with pelvis in anteversion and CMT in retroversion. The dynamic forward body projection in CP and DMD could be due to the walking-on-toe that allows a dynamic progression despite the pathological limitations. The cautious walking in the CMT could be because of the reduced foot sensitivity. Deepening the comparison between pathologic conditions help the process of data interpretation in a clinical context favoring the decision on treatments.